Characterization of The Reservoir Hydrocarbon Zones in Offshore Angola Field Using Well Log Data (The Dhaka University Journal of Earth and Environmental Sciences, 2023)
The study uses data from the Girassol-1 and Girassol-2A wells, which have been utilized to describe the reservoir hydrocarbon zones in the offshore Angola field, to characterize the reservoir via formation evaluation. In petrophysical analysis, the physical characteristics of the subsurface formation and how they interact with the fluid content are often of utmost importance. The main factors employed in reservoir characterization include lithology, porosity, permeability, shale volume, water saturation, reservoir geometry, and reservoir heterogeneity. The pay zones of the reservoir are identified, and their petrophysical characteristics are described using publicly available well-log data from the prolific hydrocarbon province Girassol of offshore Angola. The net-to-gross thickness ratio of the reservoir ranges from 77% to 94%. The effective porosity of the pay zones varies from 26% to 29%, whereas the permeability ranges from 278-471mD. The shale volume ranges from 9%-17%, and the overall water saturation ranges from 17% to 45%. The general petrophysical properties reveal that the Girassol Field contains excellent reservoirs. Water saturation estimates are indicative of hydrocarbon charges throughout the pay zone. The findings, including reservoir characteristics of offshore Angola, may help take strategy for further development, enhanced production, and exploring yet-to-find gas reserves in this area in general and implementing the acquired knowledge in hydrocarbon exploration of Bangladesh in particular.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 11(2), 2022, P 81-99